2013
DOI: 10.1088/1612-2011/11/2/025601
|View full text |Cite
|
Sign up to set email alerts
|

ZnO nanoparticles as drug delivery agent for photodynamic therapy

Abstract: Multidrug resistance (MDR) limits the success of many tumoricidal drugs. Non-significant accumulation of the drug into the target site is one major problem in photodynamic therapy. Nanoparticles are extensively used as efficient drug carriers in various local infectious and premalignant biological tissues. Due to their unique physical and chemical properties, PEGylated zinc oxide nanoparticles (ZnO NPs) exhibit high drug loading capacities, sustained drug release profiles and long-term anticancer efficacy. (Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…A greyish-white patch was formed on the top of the sample thereby indicating that the metal ions were diffused on the surface of the ZnO nanoparticles. From the SEM, as emphasized by Alam et al the server aggregated particle size was found and the results were closer to X-rd analysis [15]. The significant SEM particles dimension is higher than the corresponding crystallite size i.e.…”
Section: Scanning Electron Microscope (Sem)supporting
confidence: 72%
“…A greyish-white patch was formed on the top of the sample thereby indicating that the metal ions were diffused on the surface of the ZnO nanoparticles. From the SEM, as emphasized by Alam et al the server aggregated particle size was found and the results were closer to X-rd analysis [15]. The significant SEM particles dimension is higher than the corresponding crystallite size i.e.…”
Section: Scanning Electron Microscope (Sem)supporting
confidence: 72%
“…Many promising techniques still figured out several issues like limitations of reliable protocols such as appropriate labelling, interaction of hydrophobic and hydrophilic nanoparticles, and proper visibility of cells from data for disease recognition, to achieve a minimal damaging effect in a healthy site [61][62][63][64].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, ZnO has been reckoned as an excellent UV shielding material, characterized by photo-fastness and absorptivity over a broad UV range, in contrast to other organic and inorganic UV shielding materials [ 9 ]. Moreover, ZnO is applied to cosmetics [ 10 ], optoelectronic devices [ 11 14 ], solar cells [ 10 ], catalysts [ 15 ], energy storage (battery) materials [ 16 ], fast data storage [ 17 ], light-emitting diodes (LEDs) [ 18 ], gas sensors [ 10 ], thermoelectric devices [ 19 ], varistors [ 20 – 21 ], window materials for displays [ 21 ], laser technology [ 10 ], surface acoustic wave devices [ 22 ] and drug delivery [ 23 ].…”
Section: Introductionmentioning
confidence: 99%